The itching hand: important differential diagnoses and treatment - Weisshaar, Elke; Kallen, Ursula; Weiß, Melanie (Journal der Deutschen Dermatologischen Gesellschaft, 2013)
Skin diseases affecting the hands receive particular individual attention and constitute a considerable emotional burden. Many dermatoses also present with itching of the hands. Itch is often underestimated when it occurs in a comparably limited body area such as the hands. The high occupational significance of the hands in many professions must, nevertheless, be stressed. One of the most frequent diagnoses in itching of the hands is eczema. In the differential diagnosis, less common diseases such as neurological and systemic diseases and adverse drug reactions must also be taken into consideration. Itching of the hands can also be accompanied by other sensations, such as burning, stinging and pain. A thorough history regarding sensations and dysesthesias already allows for a diagnostic classification of the disease in some cases. Itching of the hands requires a careful and thorough diagnostic approach. This forms the basis of a specific and successful therapy which may be adapted stepwise, depending on the underlying cause, and also may require, in addition to causal therapy, symptomatic antipruritic therapy. Therapy should follow the current guidelines for chronic pruritus and hand eczema. This article reviews over the differential diagnosis and therapy of ìitching handsî.